2021
DOI: 10.1155/2021/6650469
|View full text |Cite
|
Sign up to set email alerts
|

Severity and Mortality Associated with Steroid Use among Patients with COVID-19: A Systematic Review and Meta-Analysis

Abstract: Background. There are controversial suggestions about steroid use to treat patients infected with COVID-19. Conclusive evidence regarding the use of steroids to treat COVID-19 is still lacking. This meta-analysis aimed to determine the mortality and severity associated with corticosteroid therapy compared to noncorticosteroid treatment in patients with COVID-19. Methods. The information was collected from electronic databases: PubMed, CINAHL, the Cochrane Library, clinicaltrials.gov, and Google scholar through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…In a retrospective study of 441 patients conducted prior to the COVID-19 pandemic, Kim et al ( 10 ) reported that steroid use was independently associated with increased inhospital mortality in patients successfully weaned off steroids. In addition, further analysis regarding corticosteroid use in COVID-19 remains inconclusive ( 11 ). Overall, we believe that these findings suggest that the role of steroids for COVID-19 ARDS requires additional analysis before the utilization of this therapy is confirmed in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study of 441 patients conducted prior to the COVID-19 pandemic, Kim et al ( 10 ) reported that steroid use was independently associated with increased inhospital mortality in patients successfully weaned off steroids. In addition, further analysis regarding corticosteroid use in COVID-19 remains inconclusive ( 11 ). Overall, we believe that these findings suggest that the role of steroids for COVID-19 ARDS requires additional analysis before the utilization of this therapy is confirmed in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis showed no mortality benefit with the use of corticosteroids when compared to those not on corticosteroids. [ 31 ]. A UK based study has shown a mortality benefit when corticosteroids are administered to patients on invasive mechanical ventilators.…”
Section: Resultsmentioning
confidence: 99%
“…For comparison, the equivalent to the RECOVERY trial dosing of 6 mg dexamethasone is 20-30 mg of methylprednisolone ( 16 ). Furthermore, corticosteroids were associated with an increased risk of death in patients younger than 60 years without inflammation on admission ( 17 ). Thus, the observed effect of steroids in this real-world study may diverge from the effect reported in randomized trials due to factors such as inconsistent dosing, steroid choice, and patient selection early in the pandemic.…”
Section: Discussionmentioning
confidence: 99%